2018
DOI: 10.1007/s00345-018-2461-x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral wall thickness as a significant factor in predicting spontaneous passage of ureteral stones of ≤ 10 mm: a preliminary report

Abstract: UWT can serve as a potential predictive factor for 4-week SP and may help physicians to select patients who require immediate interventions among those with ≤ 10-mm ureteral stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Previous studies reported that the prevalence of the soft-tissue rim sign did not differ between patients with spontaneous stone passage and those who failed conservative management [14],and was not associated with the stone location or degree of obstruction [13,20].However, recent research on ureteral wall thickness (UWT) suggests that the soft tissue rim sign may be associated with delayed stone passage. Yoshida et al reported that higher UWT (> 2.7 mm) is associated with failed 4-week spontaneous stone passage [21]. In our study, we considered the soft tissue rim sign as positive when there is an obviously visible rim of soft tissue surrounding the ureteral stone, suggesting that only ureteral stones with a higher UWT were categorized as having a soft tissue rim sign.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies reported that the prevalence of the soft-tissue rim sign did not differ between patients with spontaneous stone passage and those who failed conservative management [14],and was not associated with the stone location or degree of obstruction [13,20].However, recent research on ureteral wall thickness (UWT) suggests that the soft tissue rim sign may be associated with delayed stone passage. Yoshida et al reported that higher UWT (> 2.7 mm) is associated with failed 4-week spontaneous stone passage [21]. In our study, we considered the soft tissue rim sign as positive when there is an obviously visible rim of soft tissue surrounding the ureteral stone, suggesting that only ureteral stones with a higher UWT were categorized as having a soft tissue rim sign.…”
Section: Discussionmentioning
confidence: 86%
“…This is supported by the available evidence, which showed that UWT could serve as a potential predictive factor for SSP if UWT is less than 2.3 mm and may help physicians identify patients who require EI, especially if UWT is more than 2.71 mm. 17 , 18 , 22 Lastly, there is controversy in the literature regarding the role of ureteral diameter and the relation between ureteral and stone diameter in the prospect of SSP. 23 , 32 This study supports the idea that the increase in UWT and the dilatation of the urinary tract above the level of obstruction decrease the chance of SSP and promote EI.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral wall thickness (mm) (UWT): Measured as the point of greatest soft-tissue thickness around the circumference of the stone. 17 , 18 …”
Section: Radiological Variables Classificationmentioning
confidence: 99%
“…Spontaneous stone passage and downward displacement of stones were encountered in 3.8 % and 3.4% of patients with successful URS, respectively. Yoshida et al concluded that in addition to the passive ureteral dilation caused by the ureteral stent, ureteral wall thickness is a substantial factor for spontaneous passage of ureteric stones ≤ 10 mm [27]. On the contrary, it was reported that spontaneous stone passage in patients with PCN was higher than in patients with RUS [8].…”
Section: Discussionmentioning
confidence: 99%